MENTAL HEALTH WELL-BEING POLICY AND STRATEGY IN THE WORKPLACE IN THE UNITED KINGDOM (UK): LESSON TO BE LEARNED - Azmi, Ruzita; Ahmad, Siti Nur Samawati; Kamil, Bidayatul Akmal Mustafa (CENTRAL ASIA AND THE CAUCASUS, 2021)
Mental health problems in the workplace impinge on extensive diversity of interest. Such wide repercussion can be seen in the loss, which the employees suffer because they are losing job due to high absenteeism and poor performance. Family dependent on employees also suffers once they are unemployed and need to care for them if the mental illness conditions exacerbated, while the employers may endure reduction in productivity due to employees’ mental health issues. The World Health Organisation (WHO) has emphasized on the important role of the government and the employers in promoting mental health well-being at an early stage. In Malaysia, there is no specific law or policy toward mental health in the workplace, unlike the UK in the presence of the law and policy, the government has introduced Thriving at Work; an independent review, which focuses on how organizations can better support employees’ mental health. This paper aims to discuss the policy and the framework of standards embedded under the said review in the UK. It also examines on how employers can address and prevent mental illness. This paper applies qualitative method. The data are collected from primary and secondary sources derived from Acts, cases, policy papers, reports and articles from law and non-law journals, and reviews. This paper concludes that the policy and Thriving at Work introduced in the UK if emulated by companies and organizations in Malaysia not only can tackle mental illness in the workplace, indeed can be one of the preventive measures to such problems.